2003
DOI: 10.1038/sj.bjc.6601189
|View full text |Cite
|
Sign up to set email alerts
|

Improved radiotracing of oxytocin receptor-expressing tumours using the new [111In]-DOTA-Lys8-deamino-vasotocin analogue

Abstract: Oxytocin receptors (OTR) have been described in a number of tumours of different origin, and represent a new target for specific radiolabelled oxytocin (OT) analogues in cancer diagnosis and therapy. By linking the DOTA chelating agent to position 8 of the deamino derivative of Lys 8 -vasotocin (dLVT), we obtained a new compound (DOTA-dLVT) with the following characteristics: (1) it forms a monomeric and stable compound that binds to OTR with an affinity comparable to that of the endogenous OT ligand; (2) it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…4, c, d, e, and f). Doseresponse experiments indicated that DNalOVT had an EC 50 for G␣ i1 activation of 38.83 Ϯ 16.0 nM (n ϭ 3) (Fig. 5a), very similar to the 62.63 Ϯ 39.00 nM obtained using OT (Fig.…”
Section: Table 1 Ot-and Atosiban-derived Peptidessupporting
confidence: 63%
See 4 more Smart Citations
“…4, c, d, e, and f). Doseresponse experiments indicated that DNalOVT had an EC 50 for G␣ i1 activation of 38.83 Ϯ 16.0 nM (n ϭ 3) (Fig. 5a), very similar to the 62.63 Ϯ 39.00 nM obtained using OT (Fig.…”
Section: Table 1 Ot-and Atosiban-derived Peptidessupporting
confidence: 63%
“…36). The finding of the same EC 50 by means of BRET activation and IP measurements strongly validates the use of the G q biosensor in determining OTR ligand efficacy.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations